Service Quality Bus Rapid Transit JATIM, Corridor I Sidoarjo-Surabaya-Gresik - Buana, Miftahal Anjarsabda Wira; Z. A., Moh. Ah. Subhan (Majapahit Journal of Islamic Finance and Management, 2023)
There has been a significant decrease in public interest in the use of the Jatim Bus Rapid Transit (BRT) system. The present matter has a substantial impact on the decline in revenue for Perum Damri. The primary aim of this study is to evaluate the service quality of Jatim Bus Rapid Transit in Jatim, with the ultimate goal of improving public participation in this specific kind of public transportation. The results of this study reveal a significant discrepancy of -1.49, suggesting a divergence between the perceptions and anticipations of participants regarding the operating hours of the Jatim Bus Rapid Transit system. The majority of participants, comprising 64 individuals (68.1%), expressed a lack of familiarity with the operational hours of the Bus Rapid Transit (BRT) system. Additionally, they reported experiencing frequent occurrences of delayed bus arrivals at authorized bus stops. The participants conveyed their expectations regarding the clear and explicit operational hours (arrival and departure) of the Bus Rapid Transit (BRT) system. A narrower gap, tending towards zero or a positive value, signifies a heightened degree of service quality demonstrated by the organization. Conversely, when the magnitude of the gap expands, there is a corresponding decline in the degree of service quality offered by a firm. The notable decrease in the public interest and the significant discrepancy in perceptions of the Jatim Bus Rapid Transit (BRT) system’s operating hours reveals a pressing need for Perum Damri, the provider, to enhance service quality, particularly addressing issues of operational transparency and punctuality. Hence, it is crucial for service-oriented entities such as Perum Damri, the provider of the Jatim Bus Rapid Transit in Jatim, to prioritize the enhancement of service quality, with a specific focus on locations that demonstrate the most significant discrepancies as indicated by the available data.